Exogenous γ-aminobutyric Acid (GABA) Application Improved Early Growth, Net Photosynthesis, and Associated Physio-Biochemical Events in Maize - Li, Wu; Liu, Jianhua; Ashraf, Umair; Li, Gaoke; Li, Yuliang; Lu, Wenjia; Gao, Lei; Han, Fuguang; Hu, Jianguang (Frontiers in Plant Science, 2016)
γ-aminobutyric acid (GABA) is an endogenous signaling molecule and involved in growth regulations and plant development, however a little information is available on the consequences of exogenous GABA application on growth, development and associated physio-biochemical processes in maize. The present study examined the GABA-induced regulations in early growth, net photosynthetic rate, gas exchange, osmoregulation, and enzymatic activities in three maize cultivars i.e., Yuecainuo 6, Zhengtian 68, and Yuecainuo 2. Two levels of GABA i.e., 0 mg L-1 and 50mg L-1, in solution form, with total application volume of 100 ml per pot containing 15 maize seedlings were exogenously applied. Results revealed that exogenous GABA application improved seedling growth in terms of seedling length and biomass accumulation in all maize cultivars at both 3 and 7 days after treatment (DAT). It also promoted net photosynthesis and variably affected gas exchange attributes i.e., stomatal conductance (Gs), intercellular CO2 concentration (Ci), and transpiration rate (Tr), as well as leaves SPAD value. Furthermore, lipid peroxidation (in terms of malondialdehyde (MDA)) under GABA treated maize seedlings were also remained variable; however, osmolyte accumulation (protein and proline) and activities of anti-oxidants enzymes i.e., super-oxide dismutase (SOD) and peroxidase (POD) were also affected differently at both 3 and 7 DAT in all maize cultivars. Furthermore, enzymes involved in nitrogen metabolism e.g., nitrate reductase (NR) and glutamine synthetase (GS) were improved. These results suggest the involvement of GABA in various physio-metablical mechanisms which might lead to improvement in morphological growth of maize. In future, research is still needed at molecular and genetic levels to unravel the involvement of GABA-mediated regulations in growth and its associated physio-biochemical mechanisms.